Effects of different instructional methods on the acquisition of chemistry concepts of secondary three gifted students - Liew, Poh Yin. (2009)
This study was an investigation of the effectiveness of two instructional modes namely, Teaching Strategy F (TSI) and Teaching Strategy II' (TSII) on the acquisition of the redox concept of secondary three Gifted stream students in Singapore. The selfdiscovery approach was used in both TSI' and TSII' for the instruction of the redox concept. TSI incorporated metacognitive instruction while TSII did not.